A New Series of Latin Vulgate Readers - Lang, Bernhard (Vulgata in dialogue, 2025)
This review evaluates the "Latin Vulgate Readers" series, 2025, edited by Timothy A. Lee, Samuel H. Wessels, and Ryan Kaufman. The series includes a primary reader, the Book of Psalms, and the New Testament, all featuring the Clementine Vulgate text.